2021
DOI: 10.1080/19932820.2021.1883224
|View full text |Cite
|
Sign up to set email alerts
|

Corylin suppresses metastasis of breast cancer cells by modulating miR-34c/LINC00963 target

Abstract: Breast cancer is one of the cancers leading to most death cases among women and metastasis is the major cause of breast cancer mortality. In this study, Corylin, the flavonoid compound which is extracted and purified from Psoralea corylifolia L., the effect on breast cancer metastasis was investigated. Corylin showed inhibitory effect on migration and invasion abilities of breast cancer cells. Meanwhile, the epithelial-mesenchymal transition was also regulated by corylin. The long non-coding RNA LINC00963 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“… 28 Studies have indicated that miR-34c is closely related to bone metastasis of cancer. 29 Here, we found that the expression of miR-34c was inhibited after knockdown of OPN. However, the pathway through which the low expression of OPN mediates the suppression of miR-34c still needs to be further explored.…”
Section: Discussionmentioning
confidence: 77%
“… 28 Studies have indicated that miR-34c is closely related to bone metastasis of cancer. 29 Here, we found that the expression of miR-34c was inhibited after knockdown of OPN. However, the pathway through which the low expression of OPN mediates the suppression of miR-34c still needs to be further explored.…”
Section: Discussionmentioning
confidence: 77%
“…The cell migration assays were conducted by referring to previous studies, and the specific operation was as follows [ 22 , 23 ]. The upper chamber of the 24-well transwell plate (Corning, USA) was precoated with Matrigel (BD Biosciences, USA) for invasion assays, and inserts without Matrigel were used for migration assays.…”
Section: Methodsmentioning
confidence: 99%
“…Pec inhibited migration and invasion of MDA-MB-231, MCF-7 and 4T1 cells in vitro through downregulation of p-stat3, MMP-2 and MMP-9 hence inhibiting stat3 signalling pathway (Li et al, 2019). Corylin reduced migration, invasion and EMT of MCF-7 and MDA-MB-231 cells through miR-34c/LIN00963 target (Liu et al, 2021).…”
Section: Inhibition Of Migration and Invasion (Anti-metastasis)mentioning
confidence: 97%